Perspektif Sosiologi Agama - Mamlukhah Mamlukhah (Jurnal Darussalam: Jurnal Pendidikan, Komunikasi dan Pemikiran Hukum Islam, 2016)
This study discusses how the form of harmony conducted by the people of Sumber Manggis Hamlet so that there is harmony between religious communities in commemoration of religious holidays. Researchers use qualitative research methods. Data collection techniques used interview method, participant observation, and documentation, then collected data were processed and analyzed using data reduction, presentation of data, and drawing and verification of conclusion. Objects of this study include village government, religious leaders, and community Sumber Manggis Village Barurejo District Siliragung Banyuwangi District. The results of this study note that the forms of harmony among religious people in the anniversary of religious celebrations in Sumber Manggis Hamlet include mutual visits (silaturahim), mutual respect and mutual respect for other religious followers.